University Students: Preferences for Counseling Methods - Fisse, Jared; Meldrum, Helen (Indonesian Institute for Counseling, Education, and Therapy & Indonesian Counselor Association, 2024)
The mental health of university students has become an important concern escalated by pandemic-related stresses and insights into effective therapy for this population is needed. Participants (n 389) completed a survey indicating preferences regarding seeing a therapist employing methods reflecting one of three established schools of thought: psychoanalytic, person-centered, or cognitive-behavioral therapy (CBT). Analysis of results indicated that the CBT approach was the most popular method. However, when participants reacted to hypothetical dilemmas, there was evidence of some departure from the method students selected as their original preference. The CBT approach was more persistently chosen by participants who indicated an initial preference for that method. Demographic differences are reported. Commentary is offered on why college-aged participants might vary in their preferences for treatment styles and why so many maintain a propensity for CBT.